Efektivitas Metode Pembelajaran Kooperatif dalam Mencegah Bullying di Kelas Rendah - Renni Meiliani; Nur Rohmah; Prastoni Arif Darmawan; Hasrudi Adinata (Jurnal Ilmiah Wahana Pendidikan, 2026)
This classroom action research aimed to examine the effectiveness of the cooperative learning method in preventing bullying among second-grade students at SD Islam Al Fattah, Payo Lebar Village, Singkut District, Sarolangun Regency, in the 2025/2026 academic year. The study was conducted over two cycles involving 20 students. Each cycle consisted of planning, action, observation, and reflection stages. The intervention integrated structured cooperative learning activities designed to build teamwork, empathy, responsibility, and positive peer interaction. Data were collected through classroom observations, interviews, documentation, and behavior checklists, then analyzed using qualitative and quantitative techniques. The findings showed a consistent improvement in students’ cooperative behaviors and social responsibility, along with a significant reduction in bullying-related behaviors across cycles. The success indicators increased from 54% classical achievement in Cycle I to 93% in Cycle II. Students demonstrated stronger collaboration skills, greater empathy, and more supportive peer relationships. The study concludes that structured and consistent implementation of cooperative learning, supported by active teacher guidance, is effective in fostering a positive classroom climate and reducing bullying behavior in lower elementary grades.